Comparison of the Prophylactic Effect Between Acupuncture and Acupressure on Menstrual Migraine: Results of a Pilot Study - Xianmin Yu; Alan Salmoni (Medical Association of Pharmacopuncture Institute, 2018)
Objectives: To compare between acupuncture and acupressure for preventing menstrual migraine (MM). Methods: MM is one kind of migraine associated with menses in female. It is often associated with increased menstrual distress and disability, leading to decreased daily activity and quality of life. A randomized and controlled pilot study was conducted with three groups: verum acupuncture (VA) group, acupressure (AP) group, and control acupuncture (CA) group. The study lasted for 7 cycle-months, with a 1 cycle-month baseline observation (T1), a 3 cycle-month intervention (3 times per cycle-month) (T2-T4), and a 3 cycle-month follow-up (T5-T7). Outcome measures were number of migraine days, average and peak pain, total duration period of MM, and percentage of patients with ≥50% reduction in the number of MM days. Results: A total of 18 participants were included in the analysis (VA, n = 7; AP, n = 6; CA, n = 5). Both VA and AP were significantly more effective than CA for reducing MM days during the intervention period. Both VA and AP tended to be more effective than CA for reducing peak pain during the intervention period. No significant differences for the outcomes were observed among VA, AP, and CA during the follow-up period. No serious adverse events were reported. Discussion: Results of the pilot study suggest that both VA and AP could be considered as alternative and safe prophylactic interventions for MM. Register ClinicalTrials.gov Identifier: NCT02592681. Keywords: acupressure, acupuncture, menstrual migraine, prophylactic effect